1989
DOI: 10.1016/0301-5629(89)90067-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shock waves on suspended and immobilized L1210 cells

Abstract: Abstract--Ll210 mouse leukemia cells have been exposed to different doses of shock waves generated by underwater spark discharge at 18 kV in an experimental lithotripter (XL1, Dornier). Histological and flow cytometric investigations revealed severe damage and a LDso of about 420 shock waves when the cells were treated as suspensions. Cells immobilized in gelatine, however, were unaffected, indicating that secondary effects are responsible for the cellular damage. Possible mechanisms such as cavitation, jets, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…This discrepancy indicates the need for a further character- ization of the mechanism of shock wave induced cytotoxicity. Our earlier studies on the effect of shock waves on L I210 mouse leukemia cell suspensions (Briimmer et al 1989) revealed a dose-dependent decrease in the number of intact cells with a 50%-loss of cells after application of 500 SW. In these experi-ments, however, the population of intact cells contained subpopulations of nonviable cells as determined with a double staining technique and flow cytometry.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This discrepancy indicates the need for a further character- ization of the mechanism of shock wave induced cytotoxicity. Our earlier studies on the effect of shock waves on L I210 mouse leukemia cell suspensions (Briimmer et al 1989) revealed a dose-dependent decrease in the number of intact cells with a 50%-loss of cells after application of 500 SW. In these experi-ments, however, the population of intact cells contained subpopulations of nonviable cells as determined with a double staining technique and flow cytometry.…”
Section: Discussionmentioning
confidence: 94%
“…2b. Since the LDs0 for L I210 cells is about 500 SW (Briimmer et al 1989), it is not surprising that many cells could not be distinguished from untreated cells.…”
Section: Resultsmentioning
confidence: 99%
“…Viability of cells was determined by combined measurements with a cell counter (Coulter Counter D Industrial, Coulter Electronics, Hialeah, FL, USA) excluding destroyed cells, and a flow cytometer (FACS-Analyzer, Becton-Dickinson, Heidelberg, Germany) using a double staining method for viable and dead cells (Jones and Senft 1985): cells that were able to hydrolyze fluorescein diacetate (FDA) and so exhibit a green fluorescence of fluorescein were considered as viable, while cells whose membrane could not exclude the dye propidium iodide and show a red fluorescence were counted as dead (for details, see Brtimmer et al 1989). Determinations of cell diameters were performed in a FACS-Analyzer, equipped with an electrical resistance pulse sizing following the Coulter principle (Coulter 1956), and using a calibration curve for absolute particle sizes (Brenner and Htilser 1991 ).…”
Section: Methodsmentioning
confidence: 99%
“…In vitro, these secondary effects can be avoided by the immobilization of single cells or multicell spheroids in gelatin (see Figs. 3 f and 4b, d, f) [9,13]. Unter this condition, significant dose-dependent cellular damage was no longer detectable using flow cytometric techniques (Fig.…”
Section: Cell Culturesmentioning
confidence: 99%
“…We have performed some experiments on suspended and immobilized cell cultures that enable a separation of the primary and secondary effects of shock-wave treatment [8,9,12,13,41]. L 1210 cells (lymphocytic mouse leukemia) have been treated as single-cell suspensions, whereas the human cervical carcinoma HeLa as well as the mouse mammary carcinoma EMT6/Ro were exposed to shock waves as three-dimensionally grown mukicellular spheroids.…”
Section: Cell Culturesmentioning
confidence: 99%